The Geographical Patterns of City-Region Interaction: A Case Study of Varanasi. - Singh, Ravi S.; Singh, Satyendra N.; Gupta, Rajesh (National Geographical Journal of India, 2022)
Settlements in a given region are in continuous exchange as in reality no human settlement can afford to exist totally independent. Urban centres in a region attract surrounding areas in connection with a variety of services/functions which are not ubiquitously found. On the other hand, the urban centres draw a variety of goods produced in their surroundings. The urban settlements are thus in close interaction, with their surrounding areas, forming a zone of interaotion or influence. The present paper attempts to explain the nature of interaction between Varanasi and its surrounding region on the basis of data collected on the select criterion mainly through primary survey.